Design of Cesium target assembly with YH2 moderator and Gd thermal neutron shielding to produce 135Cs for LLFP transmutation study using the experimental fast reactor Joyo. (February 2022) - Tahara, Yoshihisa; Liem, Peng Hong; Takaki, Naoyuki; Chiba, Satoshi
Highlights: Design of cesium target assembly to produce 135 Cs in Joyo. Irradiation fields with properly adjusted neutron spectra are proposed. Natural Cs is used as a target material to produce the 135 Cs. The irradiation assembly uses YH2 moderator inside, and gadolinia rods at its periphery. Gadolinia rods have shown the high capability to suppress power peaks due to thermal neutrons. Abstract: In this design study, we investigated the feasibility of producing a sufficient amount of 135 Cs long-lived fission product (LLFP) in the Joyo fast reactor by irradiation of natural cesium ( 133 Cs). The irradiation is expected to contribute to providing 135 Cs sample for transmutation cross-section measurements for enhancing the accuracy of the LLFP nuclear data. Two irradiation fields, one located in the outer reflector and another one in the inner reflector which was adjacent to the core were investigated, and appropriate target subassemblies were designed by using the MCNP and FISPACT-II codes. In the inner reflector case, the YH2 moderator material was adopted for the neutron spectrum adjustment within the target subassembly. The gadolinia thermal neutron shielding is proposed to suppress the power peak of the adjacent fuel assembly. The result confirmed that a sufficient amount of 135 Cs can be produced at 1200 Effective Full Power Day (EFPD) in Joyo reactor (Mark IV core, 100 MWth).